Consumption, savings and (over-) indebtedness of portuguese families: a microdata approach - Mateus, Edite Maria Domingos (2016)
This dissertation studies the Portuguese families’ indebtedness from a micro perspective, seeking to understand which characteristics of indebted households are most determinant for their different indebtedness levels. Theoretically, our analysis is based in the traditional theories of consumption and savings that explain debt from a life-cycle perspective. Portuguese consumption habits and consequently savings kept changing over the years. The level of household indebtedness increased at a constant pace and, with the emergence of the recent economic and financial crisis, high debt levels became a problem. In this paper we present a brief description of the evolution of Portuguese economic and financial situation in latest decades, centring the description in the evolution of debt contracted to purchase the main residence, which is the key factor explaining Portuguese families’ high indebtedness levels. Using microdata from the 2010 Household Finance and Consumption Survey, we perform an econometric analysis to describe the typical Portuguese household that held debt in 2010. To determine the factors that influence the variation of debt volumes we estimate a multiple regression model, and conclude for a positive effect of income, the level of education of the head of the household and a stable employment contract and a negative effect of age in accordance to the standard economic theory.